Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1016/j.bej.2015.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic membrane bioreactors enable high rate treatment of slaughterhouse wastewater

Abstract: membrane bioreactors enable high rate treatment of slaughterhouse wastewater, Biochemical Engineering Journal http://dx. Highlights-AnMBRs are an effective technology for treatment of slaughterhouse wastewater -COD removal was consistently over 95% and was independent of OLR and HRT -Organic loading limit of 3-3.5 gCOD.L -1 d -1 was imposed by active biomass inventory -Biomass inventory in the AnMBR was limited to 40 g.L -1 (TS) to manage fouling ABSTRACT Anaerobic Membrane Bioreactors (AnMBRs) enable high spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(33 citation statements)
references
References 35 publications
2
29
0
2
Order By: Relevance
“…Most recently, laboratoryand pilot-scale AnMBR plants have been used to treat different food processing wastewater, e.g. from slaughterhouses [31], molasses production [32], dairy manure [29], pharmaceutical production [33] and landfill leachate [26]. While a number of full-scale aerobic MBR studies have been conducted on municipal or industrial wastewaters [23,[84][85][86], there has only been one study to date reporting on a full-scale AnMBR installation for industrial wastewater treatment ( [35]; Table 2).…”
Section: Anmbr Application In Industrial Wastewater Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Most recently, laboratoryand pilot-scale AnMBR plants have been used to treat different food processing wastewater, e.g. from slaughterhouses [31], molasses production [32], dairy manure [29], pharmaceutical production [33] and landfill leachate [26]. While a number of full-scale aerobic MBR studies have been conducted on municipal or industrial wastewaters [23,[84][85][86], there has only been one study to date reporting on a full-scale AnMBR installation for industrial wastewater treatment ( [35]; Table 2).…”
Section: Anmbr Application In Industrial Wastewater Treatmentmentioning
confidence: 99%
“…Dereli et al [6], Ismail et al [88] and Lefebvre and Moletta [89] have all reported high salt concentrations as one of the most serious limiting factors for anaerobic systems due to their inhibitory/toxic effects on non-adapted biomass. Following biomass adaptation, however, AnMBRs are capable of achieving very high COD removal efficiencies when fed with otherwise poorly biodegradable wastewater [31,55,90].…”
Section: One Of the Main Operational Advantages Of Anmentioning
confidence: 99%
See 1 more Smart Citation
“…Anaerobic treatment is the preferred biological treatment because of its effectiveness in treating high-strength wastewater such as SWW with less complex equipment requirements [8]. Although anaerobic treatment is efficient, anaerobically treated effluents require posttreatment to comply with required discharge limits where the complete stabilization of the organic matter is not possible by anaerobic treatment alone.…”
Section: Introductionmentioning
confidence: 99%
“…Changes observed in bacterial and archaeal richness did not match with the functioning of the system. However, dynamics and evenness parameters seemed to be of importance in maintaining a stable reactor performance Jensen et al (2015). used an anaerobic membrane bioreactors (AnMBR) for the removal of over 95% of the COD from the wastewater generated by cattle slaughterhouses.…”
mentioning
confidence: 99%